The Influence of Public Perception and Social Acceptance of Plastic Bag Ban Policies on Their Management Practices in Rwanda: A Case Study of Musanze District - Manishimwe Merveille; Eric Sibomana; Richard Mind’je (East African Journal of Environment and Natural Resources, 2026)
This study investigated the influence of public perception and social acceptance of Rwanda’s plastic bag ban on environmental management practices in Musanze District. Using a mixed-methods approach, data were collected from 379 survey respondents, key informant interviews, observations, and secondary sources. Key findings revealed high levels of awareness (M = C–4.41), positive attitudes (M = 4.36–4.46), and strong social acceptance (M = 4.28–4.36) of the ban. Environmental management practices were also strong, including high compliance with the ban, proper waste disposal, and active community participation. Statistical analysis showed strong positive correlations (r = 0.76–0.89) between perception variables and management practices. Regression models indicated that public perception strongly predicted compliance (R² = 0.91) and community participation (R² = 0.89). The study concludes that enhancing awareness, enforcement, and access to affordable alternatives is essential to strengthen the effectiveness of plastic bag ban policies in Rwanda